Electrospun biocomposite polycaprolactone/collagen tubes as scaffolds for neural stem cell differentiation - Hackett, Joanne M.; Dang, ThucNhi T.; Tsai, Eve C.; Cao, Xudong (Université d'Ottawa | University of Ottawa, 2010)
Studies using cellular therapies, scaffolds, and tubular structured implants have been carried out with the goal to restore functional recovery after spinal cord injury (SCI). None of these therapeutic strategies, by themselves, have been shown to be sufficient to achieve complete restoration of function. To reverse the devastating effects of SCI, an interdisciplinary approach that combines materials science and engineering, stem cell biology, and neurosurgery is being carried out. We are currently investigating a scaffold that has the ability to deliver growth factors for the proliferation and differentiation of endogenous stem cells. Neural stem cells (NSCs) derived from mice are being used to assess the efficacy of the release of growth factors from the scaffold in vitro. The fabrication of the tubular implant allows a porous scaffold to be formed, which aids in the release of growth factors added to the scaffold.
Keywords: differentiation; electrospun nanofibers; nerve tissue engineering; neurospheres